Towards Industry 4.0: increasing efficiency and effectiveness through technology integration in agriculture - Tiwari, Siddhartha Paul (Management and Entrepreneurship: Trends of Development, 2023)
Agricultural industries, as well as other industries, are experiencing profound changes as a result of Industry 4.0. A key enabler technology that is becoming increasingly incorporated into agricultural equipment is a combination of cyber-physical systems, machine learning, the Internet of things, robots, artificial intelligence, the cloud, and cognitive computing, which are all key enabler technologies that allow the agricultural sector to achieve this transformation. The study involved interviews and surveys of 250 professionals from a cross-section of the agriculture industry and emerging technologies. According to the results, advances in machinery have led to a considerable increase in the scale, speed, and productivity of farm equipment, which has resulted in more efficient farming. A significant improvement has also been made in the quality of seeds, resources, irrigation, and fertilizer used by farmers over the years, allowing them to increase their yields. As a conclusion, the concept of artificial intelligence (AI) is at the heart of Industry 4.0. AI has an important role to play in agriculture. JEL Classification: O14, O32, O33